2007
DOI: 10.1007/s10592-007-9368-1
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite and mitochondrial DNA variation defines island genetic reservoirs for reintroductions of an endangered Australian marsupial, Perameles bougainville

Abstract: Natural populations of the endangered western barred bandicoot (Perameles bougainville) now exist on only two islands in Shark Bay, Western Australia. Our aim was to investigate genetic diversity in natural, reintroduced, and captive populations of the bandicoots and to assess the extent of divergence between the populations. The contemporary isolation of the natural populations has resulted in heterogeneity of allele frequency between the islands, which has acted to maintain a higher combined diversity than w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 66 publications
2
21
0
Order By: Relevance
“…90% of the mean H e in wild populations). We only found one exception (Western barred bandicoot: Perameles bougainville), in which H e was low (0.27) despite the number of 30 founders (Smith and Hughes 2008). However, in this case the sampling of the captive population was rather low (N = 8) and H e was also low in the wild populations.…”
Section: Discussionmentioning
confidence: 66%
“…90% of the mean H e in wild populations). We only found one exception (Western barred bandicoot: Perameles bougainville), in which H e was low (0.27) despite the number of 30 founders (Smith and Hughes 2008). However, in this case the sampling of the captive population was rather low (N = 8) and H e was also low in the wild populations.…”
Section: Discussionmentioning
confidence: 66%
“…A recent study by Smith and Hughes (2007a) found genetic diversity levels in the WBB, estimated by genotyping six microsatellite loci across 134 individuals from 5 populations (Bernier and Dorre…”
Section: Evaluation Of Risk or Susceptibility To Bpcv1 Infection And mentioning
confidence: 99%
“…Islands, Heirisson Prong, the PCBC and Dryandra), to be amongst the lowest ever recorded for a population of marsupials (Smith and Hughes 2007a). Reduced genetic diversity may increase susceptibility of a species to novel diseases, environmental stresses and, ultimately extinction (World Conservation Monitoring Centre 1992;Frankham 1997;Smith and Hughes 2007a).…”
Section: Evaluation Of Risk or Susceptibility To Bpcv1 Infection And mentioning
confidence: 99%
See 2 more Smart Citations